Juvenile hormone signaling during reproduction and development of the linden bug, Pyrrhocoris apterus - Smykal, Vlastimil; Bajgar, Adam; Provaznik, Jan; Fexova, Silvie; Buricova, Marcela; Takaki, Keiko; Hodkova, Magdalena; Jindra, Marek; Dolezel, David (Insect biochemistry and molecular biology, 2014)
Juvenile hormone (JH), a sesquiterpenoid produced by the insect corpus allatum gland (CA), prevents metamorphosis in larvae and stimulates vitellogenesis in adult females. Whether the same JH signaling pathway regulates both processes is presently unknown. Here, we employ the robust JH response during reproduction and development of the linden bug, Pyrrhocoris apterus, to compare the function of key JH-signaling genes encoding the JH receptor, Methoprene-tolerant (Met), its binding partner Taiman (Tai), and a JH-inducible protein, Krüppel-homolog 1 (Kr-h1). RNA interference (RNAi) with Met or Tai, but not Kr-h1, blocked ovarian development and suppressed vitellogenin gene expression in the fat body of females raised under reproduction-inducing conditions. Loss of Met and Tai matched the effects of CA ablation or the natural absence of JH during reproductive diapause. Stimulation of vitellogenesis by treatment of diapausing females with a JH mimic methoprene also required both Met and Tai in the fat body, whereas Kr-h1 RNAi had no effect. Therefore, the Met-Tai complex likely functions as a JH receptor during vitellogenesis. In contrast to Met and Kr-h1 that are both required for JH to prevent precocious metamorphosis in P. apterus larvae, removal of Tai disrupted larval ecdysis without causing premature adult development. Our results show that while Met operates during metamorphosis in larvae and reproduction in adult females, its partner Tai is only required for the latter. The diverse functions of JH thus likely rely on a common receptor whose actions are modulated by distinct components.
Keywords: Sexual Behavior, Animal; shazování tělního pokryvu; Juvenile Hormones; Diapause, Insect; Molting; Methoprene-tolerant; Diapause; Vitellogenesis; Reproduction; signální transdukce; sexuální chování zvířat; bHLH-PAS; Signal Transduction; rozmnožování; diapauza hmyzu; larva; Animals; zvířata; Larva; juvenilní hormony; Metamorphosis; Heteroptera; Oogenesis